Selective electrochemical oxidation of organic compounds in a mass transfer-enhanced electrochemical flow reactor (e-NETmix) - Rosa, CH (2024)
e(-)NETmix stands as an electrochemical flow reactor engineered to enhance mass transfer. This study aimed at assessing the performance of the e(-)NETmix reactor in the realm of organic electrosynthesis. Specifically, the research focused on the selective electrochemical oxidation of 4-methoxybenzyl alcohol (4-MBA) to p-anisaldehyde (PAA) using a bare fluorine-doped tin oxide (FTO) anode. The efficiency of the process was assessed for distinct current densities (j), Reynolds numbers (Re), supporting electrolyte contents, and substrate initial contents. The e(-)NETmix reactor was extensively compared to a commercial electrochemical flow reactor (MicroFlowCell from ElectroCell, Denmark). e(-)NETmix facilitated the use of a broader range of j (0.8-2.0 mA cm(-2) versus 0.8 mA cm(-2)) together with smaller Re (>= 190 versus >1750), supporting electrolyte contents (>= 1 mM versus >= 30 mM), and substrate initial contents (>= 2.0 mM versus >= 3.0 mM) with no loss of PAA production or energy consumption. These findings underscore a remarkable suitability of e(-)NETmix as a reactor for organic electrosynthesis.